Corrigendum: Drought Stress Responses and Resistance in Plants: From Cellular Responses to Long-Distance Intercellular Communication - Takahashi, Fuminori; Kuromori, Takashi; Urano, Kaoru; Yamaguchi-Shinozaki, Kazuko; Shinozaki, Kazuo (Frontiers in Plant Science, 2021)
The drought stress responses of vascular plants are complex regulatory mechanisms because they include various physiological responses from signal perception under water deficit conditions to the acquisition of drought stress resistance at the whole-plant level. It is thought that plants first recognize water deficit conditions in roots and that several molecular signals then move from roots to shoots. Finally, a phytohormone, abscisic acid (ABA) is synthesized mainly in leaves. However, the detailed molecular mechanisms of stress sensors and the regulators that initiate ABA biosynthesis in response to drought stress conditions are still unclear. Another important issue is how plants adjust ABA propagation, stress-mediated gene expression and metabolite composition to acquire drought stress resistance in different tissues throughout the whole plant. In this review, we summarize recent advances in research on drought stress responses, focusing on long-distance signaling from roots to shoots, ABA synthesis and transport, and metabolic regulation in both cellular and whole-plant levels of Arabidopsis and crops. We also discuss coordinated mechanisms for acquiring drought stress adaptations and resistance via tissue-to-tissue communication and long-distance signaling.